Postpartum hepatitis and host immunity in pregnant women with chronic HBV infection - Zhang, Lu; Jiang, Tingting; Yang, Ying; Deng, Wen; Lu, Huihui; Wang, Shiyu; Liu, Ruyu; Chang, Min; Wu, Shuling; Gao, Yuanjiao; Hao, Hongxiao; Shen, Ge; et al. (Frontiers in Immunology, 2023)
In order to develop immune tolerant to the fetal, maternal immune system will have some modification comparing to the time before pregnancy. Immune tolerance starts and develops at the maternal placental interface. In innate immunity, decidual natural killer (dNK) cells, macrophages and dendritic cells play a key role in immue tolerance. In adaptive immunity, a moderate increase of number and immune inhibition function of regulatory T cells (Treg) are essential for immune tolerance. The trophoblast cells and immune cells expressing indoleamine 2,3-dioxygenase (IDO), the trophoblast cells expressing HLA-G, and Th1/Th2 shifting to Th2 dominant and Th17/Treg shifting to Treg domiant are in favor of maternal fetal immune tolerance. Steroids (estrogen and progesterone) and human chorionic gonadotropin (HCG) also participate in immune tolerance by inducing Treg cells or upregulating immunosuppressive cytokines. Most of the patients with chronic HBV infection are in the "HBV immune tolerance period" before pregnancy, and the liver disease is relatively stable during pregnancy. In chronic HBV infection women, after delivery, the relative immunosuppression in vivo is reversed, and Th1 is dominant in Th1/Th2 and Th17 is dominant in Th17/Treg balance. After delivery, the number of Treg decrease and NK cells increase in quantity and cytotoxicity in peripheral blood. Liver NK cells may cause liver inflammation through a non-antigen specific mechanism. After delivery, the number of CD8+ T cells will increase and HBV specific T cell response recovers from the disfunction in pregnancy. Under the background of postpartum inflammation, the rapid decrease of cortisol after delivery, and especially the enhancement of HBV specific T cell response induced by HBV DNA and cytokines, are the main reasons for postpartum hepatitis. HBeAg positive, especially HBeAg<700 S/CO, and HBV DNA>3-5Log10IU/ml are risk factors for postpartum hepatitis. Antiviral treatment in late pregnancy can reduce the incidence of mother to child transmission (MTCT) in chronic HBV infection women. Chronic HBV infection women have hepatitis both during pregnancy and more often in 12 weeks postpartum. It is generally agreed that postpartum hepatitis is mild symptoms and self-limited. Delaying drug withdrawal to 48 weeks can increase the seroconversion rate of HBeAg in delivery women